Farm Road Infrastructure Development and Change Social Community Economy in the Village - M Ihsan Darwis (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
The objectives of the study were to determine the effect of the development of Jalan Tani infrastructure on the socio-economic changes of the community in Mombi Village, Alu Subdistrict, Polewali Mandar Regency, how is the role of the government in developing Farmer Road infrastructure in Mombi Village, Alu Subdistrict, Polewali Mandar Regency. The results of the study show the effect of infrastructure development on socio-economic changes in society in general. The livelihoods of the people in Mombi Village, Alu District, Polewali Mandar Regency before and after the construction of Jalan Tani, do not highlight significant changes,It is understood that the government has an important role in the development process. Apart from being a distributor of development funds, the government also has a role as an agent who provides direction on the development of farm road infrastructure and provides solutions to the community if there are obstacles in development. The level of community education prior to the existence of Jalan Tani in Mombi Village is better educational facilities after the construction of Jalan Tani, educational services are more fulfilled.